The Sweetpotato Genome - Yencho, G. Craig; Olukolu, Bode A.; Isobe, Sachiko; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2025)
This open access book is a compilation of advances in sweetpotato genomics, which have been used to improve our understanding of the evolution of sweetpotato, increase our knowledge of crop growth and development, and provided critical information required for genomic-assisted breeding in sweetpotato. Sweetpotato is a critical food staple for millions of people in the developing world that has long been considered an under-resourced, orphan crop. However, this perception is changing, and significantly, more resources have been devoted to the improvement of sweetpotato in both the private and public sectors around the world during the last decade. Its twelve chapters review the changing food security and commercial food product landscape of sweetpotato in the developed and developing world, global wild and cultivated genome sequencing efforts in sweetpotato, the evolution of molecular markers and the development of novel polyploid linkage mapping, quantitative trait loci and genomic selection strategies required for gene discovery in this complex crop, and the use of these new tool in sweetpotato crop improvement programs around the globe. This book is useful to students, teachers, and scientists in universities, research institutes, and private companies. .
Keywords: Botany; Genetics; Agriculture; Plant Science; Genetics and Genomics; Agriculture